Work Readiness among Final Year Students in A Higher Education in Malaysia - Rahman, Alias; Guan Teik, Ee; Agnis, Sombuling; Samsiah, Jayos (Human Resource Management Academic Research Society, 2022)
This study was conducted to examine the level of work readiness among final year students at a public university in Malaysia. A total of 71 respondents participated in this study (N = 71), consisting of 22.5% (16) males and 77.5% (55) females. The level of work readiness was measured using the Work Readiness Inventory which looked at six areas of work readiness, namely Responsibility, Flexibility, Skills, Communication, Self-view and Health & safety. The results of this study showed that all of the students have high work readiness in all areas, except Self-view has a moderate work readiness. Out of the six areas of work readiness, only Self-view had a significant difference between genders, t = 2.46, k <.05, where male students have a higher level of work readiness (M = 3.20, SD= 0.62) than female students (M = 2.79, SD= 0.51). This study revealed that the university must act proactively and promptly as a nurture place to brush up students’ self-efficacy, especially among female students.